Confirmation of Valeriana nivalis (Valerianaceae) to the Argentinian flora - Zanotti, Christian A.; Suescún, Mabel A.; Acosta, Juan M. (Phytotaxa, 2014)
We confirm the occurrence of Valeriana nivalis to the Argentinean flora, based on results of both morphological and molecular phylogenetic studies. We also include a taxonomic description, distribution, and additional information to discern V. nivalis from V. pycnantha.